1986
DOI: 10.1111/j.1439-0523.1986.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Compatibility/Incompatibility in Some Orchids of the Subfamily Vandoideae

Abstract: Self‐pollination of 2f species of vandaceous orchids was followed by later embryo culture carried out to determine which species are self‐compatible (SC) or incompatible (SI): 10 are SC, 1 are SI and the remaining:8 require further study. In the SI species, a few progeny could usually be recovered and these are interpreted as arising from mutation at the incompatibility locus (loci). The implications of the findings for current models of incompatibility are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…The incidence and extent of SI in many outbreeding orchid genera is still not known or poorly understood. However, the previous low estimates of SI in the Orchidaceae are proving to be inaccurate, and a growing volume of literature suggests that SI is widespread in both New and Old World orchid genera (Charanasri and Kamemoto, 1977; Stort and de Lima Galdino, 1984; Agnew, 1986; Johansen, 1990; Christensen, 1992; Borba et al, 2002; Blanco and Barbosa, 2005; Tremblay and Ackerman, 2007; Barbosa et al, 2009; Cheng et al, 2009; Gontijo et al, 2010). While within the Pleurothallidinae, a recent study (Borba et al, 2011) has identified the operation of SI in seven of the main clades of Pleurothallidinae (Pridgeon and Chase, 2001), and the current study has confirmed the operation of SI in the remaining clade, namely clade B (Pridgeon and Chase, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and extent of SI in many outbreeding orchid genera is still not known or poorly understood. However, the previous low estimates of SI in the Orchidaceae are proving to be inaccurate, and a growing volume of literature suggests that SI is widespread in both New and Old World orchid genera (Charanasri and Kamemoto, 1977; Stort and de Lima Galdino, 1984; Agnew, 1986; Johansen, 1990; Christensen, 1992; Borba et al, 2002; Blanco and Barbosa, 2005; Tremblay and Ackerman, 2007; Barbosa et al, 2009; Cheng et al, 2009; Gontijo et al, 2010). While within the Pleurothallidinae, a recent study (Borba et al, 2011) has identified the operation of SI in seven of the main clades of Pleurothallidinae (Pridgeon and Chase, 2001), and the current study has confirmed the operation of SI in the remaining clade, namely clade B (Pridgeon and Chase, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although studied in many angiosperm families, SI is often considered relatively rare in the Orchidaceae, with most species being self-compatible and "avoiding" self-pollination by other means ( Agnew, 1986 ;Dressler, 1990Dressler, , 1993Borba and Semir, 1999 ;Singer and Cocucci, 1999 ;Borba et al, 2001 ;Ingrouille and Eddie, 2006 ;Roberts, 2003 ;Gontijo et al, 2010 ). Dressler (1990Dressler ( , 1993 ) estimated SI to occur in 10% of orchid species, but considered its full extent still to be established ( Dressler, 1993 ).…”
mentioning
confidence: 99%
“…1982; Ackerman & Oliver 1985; Kjellsson et al. 1985; Agnew 1986; Kjellsson & Rasmussen 1987; Clifford 1988; Johansen 1990), the family is thought to be largely self‐compatible.…”
Section: Discussionmentioning
confidence: 99%
“…Ackerman (1986) showed that tropical orchids have generally smaller population sizes and suggested that this may reduce their ability to sustain pollinators, even when a reward is present. Self-incompatibility, although uncommon in orchids (Calder et al 1982;Ackerman and Oliver 1985;Kjellson et al 1985;Agnew 1986;Kjellson and Ramussen 1987;CliVord 1988), is usually also associated with very low levels of fruit set (Neiland and Wilcock 1998). However, the combined impact of habit, Xoral traits and population size on the reproductive success of tropical orchids has not so far been studied.…”
Section: Introductionmentioning
confidence: 94%